The Challenge of Improving Homework Processes and Benefits: Insights from Two Intervention Research Sessions with Teachers and Parents of an Elementary School - Deslandes, Rollande; Barma, Sylvie (International Journal about Parents in Education, 2023)
This paper is in line with our prior works conducted mainly on parents and teachers’ points of view regarding homework. In Quebec, Canada, homework is perceived as a near-universal practice. However, school communities are strongly urged to engage in a collective reflection over homework at a local level in order to document the different avenues that could embrace the main stakeholders’ concerns. This paper investigates how teachers and parents can act as agents of change in such a process. The research-intervention was based on Cultural-Historical Activity Theory using the Change Laboratory methodology. It draws upon the concept of expansive learning and suggests that participants agree with the nature of the problem and model together new solutions. The present study focuses on the transformative agentic actions that were put into place during two Change Laboratory sessions. This analysis deepens our understanding of teachers’ role and expectations towards parents as well as parents’ comprehension of the teachers’ role and of their own role in the context of their child’s homework. The authors conclude that there is a need to have teachers, parents and the school principal engage with one another to develop a common vision of the issues at stake.